2022
DOI: 10.31545/intagr/144951
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical methods used to generate tolerance to drought stress in seeds and plants: a review

Abstract: Drought stress has serious repercussions for agriculture, affecting crop growth with low yield effects concerning food production and food security. The main objective of this research is to conduct a scientific literature review of the physical methods used to generate tolerance to water stress in crops. (i) The most widely applied physical method to counteract the effects of drought stress is UV radiation, magnetic field application (18%), He-Ne and CO 2 laser (18%), gamma radiation (9%) and plasma (6%). (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 96 publications
0
5
0
6
Order By: Relevance
“…Был обнаружен эффект последействия предпосевной обработки семян физическими стрессорами, выражающийся в повышении устойчивости растений к определенным видам стресса (засуха, засоление и др.). В частности, установлено, что обработка семян ультрафиолетовым и гамма-излучением впоследствии повышает засухоустойчивость растений [59]. Это делает перспективным рассмотрение эффекта физической предпосевной обработки семян в связи с вновь открытым явлением стрессовой эпигенетической памяти растений.…”
Section: физические эустрессоры как средство стимулирования прорастан...unclassified
See 1 more Smart Citation
“…Был обнаружен эффект последействия предпосевной обработки семян физическими стрессорами, выражающийся в повышении устойчивости растений к определенным видам стресса (засуха, засоление и др.). В частности, установлено, что обработка семян ультрафиолетовым и гамма-излучением впоследствии повышает засухоустойчивость растений [59]. Это делает перспективным рассмотрение эффекта физической предпосевной обработки семян в связи с вновь открытым явлением стрессовой эпигенетической памяти растений.…”
Section: физические эустрессоры как средство стимулирования прорастан...unclassified
“…Предпосевная обработка для улучшения всхожести (прайминг) -это хорошо известная операция для улучшения качества семян, являющаяся эффективным средством увеличения их всхожести, синхронизации прорастания, а также улучшения роста проростков в неблагоприятных условиях, что способствует увеличению урожайности сельскохозяйственных растений [1]. Для предпосевной обработки семян активно используют способы воздействия, основанные на физических эффектах, таких как микроволновое и ультрафиолетовое излучение, ионизирующие излучения, магнитное поле [1,59].…”
Section: Introductionunclassified
“…The development of ramie cultivars which are tolerant to environmental stresses is a critical need at this time ( Wu et al, 2021b ). Developing crop genotypes with improved agronomic traits that offer resistance to abiotic stresses has long been an international concern ( Romero-Galindo et al, 2022 ). The first step is to adopt reasonable practices under changing environmental conditions.…”
Section: Molecular Techniques To Enhance Drought Tolerance In Ramiementioning
confidence: 99%
“…Studies using various crops have confirmed, for example, the stimulating effect of bioactive compounds in pre-sowing seeds and in seedlings or plants during their development (Bera et al, 2022). Both ionizing and non-ionizing physical methods are promising techniques to use in the seed priming stage in order to improve seed quality parameters (sanitary, physiological, nutritional, genetic), reduce agrochemical use during cultivation and increase the tolerance to stress in agricultural crops (Romero et al, 2021). However, to fulfil a specific purpose or priority, it is necessary to find and optimize the radiation parameters that are used.…”
Section: Introductionmentioning
confidence: 99%